The Influence of Authentic Leadership and Work Environment with Job Satisfaction as a Mediating Variable on Employee Performance in Construction Company PT. XYZ - Kusuma, Awang Pandhu; Wanasida, Albert Surya (Transpublika Publisher, 2025)
The primary objective of this research is to examine the impact of genuine leadership and the working environment on employee productivity, with job contentment as a intervening factor, at PT XYZ, a construction firm. A quantitative method was employed, involving the distribution of questionnaires to 50 PT XYZ employees for data collection. The connection between variables was examined using the PLS-SEM approach. The outcomes indicated that the working environment has a favourable and noteworthy effect on job satisfaction, while genuine leadership does not significantly influence job satisfaction or employee productivity. Moreover, job satisfaction does not serve as a mediator between the two independent variables and employee performance. The implication of this research highlights the significance of enhancing genuine leadership styles to promote a positive working environment and enhance overall employee productivity.